SYNTHESIS, PREPARATIVE SEPARATION OF STRUCTURE ISOMERS AND PROPERTIES OF 2-(2-(DIALKYLAMINO)ETHYLAMINO)ETHANOLS OF ARYLALIPHATIC SERIES - D. Q. Hoang; E. Ya. Borisova; N. Yu. Borisova; A. V. Krylov; N. A. Danilkin; A. G. Samokhin (Тонкие химические технологии, 2017)
A method for the synthesis of 2-(2-(dialkylamino)ethylamino)ethanols based on the epoxide ring opening in styrene oxide by N,N-disubstituted ethylenediamines was developed. It is shown that the opening of the oxirane ring by diamines in 2-propanol at room temperature occurs mainly according to the Krasusky rule at the bond between the oxygen atom and the less substituted carbon atom. A mixture of two products with the predominance of the secondary diamino alcohol up to 82% was obtained. It was found that the separation of the products by distillation or recrystallization does not allow obtaining pure isomers. The mixture of isomers was converted into dihydrochlorides by dry HCl in dioxane and diethyl ether. Pure 2-(2-(dialkylamino)ethylamino)-1-phenylethanols and 2-(2-(dialkylamino)ethylamino)-2-phenylethanols were separated by the first fractional recrystallization of a mixture of diaminoalcohol dihydrochlorides from a mixed solvent followed by alkalization of the products with an aqueous sodium hydroxide solution. The diamino alcohols were characterized by FT-IR, 1H- and 13C-NMR and HRMS-ESI.